2013
DOI: 10.1097/opx.0000000000000008
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Comfort and Adverse Events on Contact Lens Performance

Abstract: Both subjective comfort responses and AE rates varied according to the combination of lens type and care system in use. The combinations with the best comfort ratings did not necessarily have a favorable AE rate. Practitioners can maximize behavior with respect to both these factors by choosing an appropriate care system for the lenses they prescribe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…However, the ocular comfort and dryness response encountered after 12 hours of contact lens wear in this study was similar to that widely reported as a common experience with different contact lens types. 3,13,18,19 The addition of other contact lens types to a crossover study design will run the risk of a higher discontinuation rate of study participants, which might influence the study outcome.…”
Section: Figurementioning
confidence: 99%
“…However, the ocular comfort and dryness response encountered after 12 hours of contact lens wear in this study was similar to that widely reported as a common experience with different contact lens types. 3,13,18,19 The addition of other contact lens types to a crossover study design will run the risk of a higher discontinuation rate of study participants, which might influence the study outcome.…”
Section: Figurementioning
confidence: 99%
“…Daily disposable lenses have become the lens of first choice for many lens wearers, and in 2020 represented 63 % of soft lenses fitted. Daily disposable lenses are presumably preferred as a result of greater convenience (lens care systems being obviated) from the perspective of the wearer [23], and superior physiological response, as demonstrated by clinical trials [24] and epidemiological studies [25].…”
Section: Contact Lens Replacement Frequenciesmentioning
confidence: 99%
“…240 Bioburden and specific lens care products or modalities may play a role in the development of CIEs, yet there appears to be no advantage to the use of antibiotics to reduce the incidence of CIEs during extended wear of silicone hydrogel lenses. [241][242][243][244][245] The exact relationship between CIEs and microbial keratitis remains unclear.…”
Section: Complicationsmentioning
confidence: 99%